ENABLE-TAAT Open Day for Youth and Farmers in Uganda - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
Recently in Uganda, the Youth compact of the Technologies for African Agricultural Transformation (TAAT), also known as ENABLE TAAT, facilitated an open convergence of the government, NGOs, youth in agribusiness, credit institutions, and extension workers in Kyotera District. The aim was to showcase youth innovation across agricultural value chains.